EFEKTIVITAS PELATIHAN DOKTER GIGI KECIL UNTUK MENINGKATKAN KEBERSIHAN GIGI DAN MULUT - Ni Made Sirat; Asep Arifiin Senjaya; Ni Nengah Sumerti (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2019)
A small dentist cadre is an individual who has been organized for a certain period of time and has been continuously upgraded to achieve a goal of improving the quality of oral and dental health. The underlying importance of small dentist training activities is the school age group (6-18 years old) which is a large part of the Indonesian population (± 29%), it is estimated that 50% of these are children in the stage of growth and development so that still easy to build and mentored. Purpose of research: to know the effectiveness of small dentist training to improve dental hygiene of students of SDN 1 Kerobokan Badung Regency 2017. Research Method: This research is done by quasi experimental (experimental kwasi), pre and post test design without control. Research population: all students of grade V and VI SDN 1 Kerobokan totaling 204 people. Data analysis: Bivariate analysis with related comparative test (ordinal scale) with Wilcoxon test using Statistical Product and Service Solution (SPSS) 17.0 for Windows. Result of research: Based on the result of examination of 204 research subjects the minimum value of OHI-S is 0,16 and maximum 3,00 with mean of OHI-S value of elementary school student. 1 Kerobokan of 1.09 ± 0.52. The results of OHI-S examination after small dentist training at least the OHI-S value of 0.00 and maximum 3.00 with the average OHI-S value of 0.67 ± 0.52. Conclusion: there are differences in OHI-S values before and after small dentist training in Primary School No. 1 Kerobokan of Badung Regency, from 124 people (60,78%) to 179 people (87,75%) have OHI-S with good criterion. It is hoped the school knows the benefits of small dentist training and further enhances the role of educators in communicating dental and oral hygiene knowledge to students and UKGS activities more routinely.